THE SUSTAINABILITY OF AGRITOURISM IN ROMANIA IN THE OPINION OF PENSION ADMINISTRATORS - Georgiana Tatiana Bondac; Andreiana Violeta-Andreea; Stoica Georgiana Daniela (Ekonomika Poljoprivrede (1979))
Sustainable tourism should encompass all tourism forms, support local communities, and protect the environment while meeting diverse tourist demands. Agritourism offers a viable alternative, with growing interest in rural areas and eco-friendly agricultural products. This study analyzes agritourism sustainability by evaluating the share of self-produced agricultural consumption in guesthouses, based on a survey among administrators from five key Romanian counties: Argeș, Brașov, Dâmbovița, Prahova, and Teleorman. Results highlight the critical role of ecological products and green strategies in promoting sustainable tourism behavior. The findings underline the need to integrate cultural and ecological elements into tourism to foster responsible practices. This research offers tourism managers and policymakers a practical foundation for encouraging environmentally conscious tourism development and supporting green consumption.